1980
DOI: 10.2118/8235-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluid Saturation on Waves in Porous Rock and Relations to Hydraulic Permeability

Abstract: Detailed and very accurate measurements of compressional Vp and shear Vs wave velocities and their attenuation in dry, partly saturated and fully saturated clay-bearing sandstone were carried out at 20, 145, and 198 degrees C, under variable confining and pore pressures.The velocity results show that water saturated rock has high Vp and relatively low Vs not only at room temperature but also at 145 and 198 degrees C. Varying the pore pressure reveals that the transition from the fully saturated to the dry stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…In addition, the results obtained in this paper confirm that n k is constant and higher than 1.0 in sandstones with a substantial amount of clays (Zoback and Byerlee, 1975;Nur et al, 1980;Berryman, 1992;Al-Wardy and Zimmerman, 2004). From X-ray analysis data, the clay content in the sandstone samples was more than 10%.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In addition, the results obtained in this paper confirm that n k is constant and higher than 1.0 in sandstones with a substantial amount of clays (Zoback and Byerlee, 1975;Nur et al, 1980;Berryman, 1992;Al-Wardy and Zimmerman, 2004). From X-ray analysis data, the clay content in the sandstone samples was more than 10%.…”
Section: Discussionsupporting
confidence: 74%
“…Three groups of experimental results can be summarized: 1) n k equals 1.0 (Brace et al, 1968;Coyner, 1984;Bernabé, 1987). 2) n k ranges from 0 to 1.0 (Nur et al, 1980;Bernabé, 1986;Warpinski and Teufel, 1992;Z heng et al, 2008;Li and Xiao, 2008;Li et al, 2009a;2009b). Nur et al (1980) studied two artificial rocks and observed that n k were constant (n k values of 0.43 and 0.86) while the others found that n k varied with confi ning pressure and pore pressure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies on both sedimentary and crystalline rocks can be found in the literature. Most of the studies on sedimentary rocks have been conducted on clay-rich sandstones [7][8][9][10][11][12][13], and resulted in effective stress coefficients which are greater than one and which increase with the clay content. The evaluated effective stress coefficient by Walls [11] varies from 1.2 for clean sandstone to 7.1 for sandstone containing 20% clay.…”
Section: Introductionmentioning
confidence: 99%